2012
DOI: 10.1175/jcli-d-11-00288.1
|View full text |Cite
|
Sign up to set email alerts
|

Regimes of Diurnal Variation of Summer Rainfall over Subtropical East Asia

Abstract: Using hourly rain gauge records and Tropical Rainfall Measuring Mission 3B42 from 1998 to 2006, the authors present an analysis of the diurnal characteristics of summer rainfall over subtropical East Asia. The study shows that there are four different regimes of distinct diurnal variation of rainfall in both the rain gauge and the satellite data. They are located over the Tibetan Plateau with late-afternoon and midnight peaks, in the western China plain with midnight to early-morning peaks, in the eastern Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 52 publications
3
67
0
1
Order By: Relevance
“…These data are averaged in case of multiple passes within 3 h time window for a given grid box [Huffman et al, 2007]. A simple methodology has been adopted to combine the MW and IR estimates, and rain gauge data are used for correction over land [Yuan et al, 2012].…”
Section: Trmm 3b42 Rainfallmentioning
confidence: 99%
“…These data are averaged in case of multiple passes within 3 h time window for a given grid box [Huffman et al, 2007]. A simple methodology has been adopted to combine the MW and IR estimates, and rain gauge data are used for correction over land [Yuan et al, 2012].…”
Section: Trmm 3b42 Rainfallmentioning
confidence: 99%
“…The nocturnal precipitation in the Sichuan Basin in summer, i.e. the precipitation reaches its diurnal peak around midnight, becomes a hot topic in the recent decade (Li et al 2008;Yu et al 2007aYu et al , 2009Chen et al 2010;Huang et al 2010;Bao et al 2011;Yuan et al 2011). This phenomenon has been observed and documented since long time (Lu 1942;Ye and Gao 1979;Zeng et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (2007b) and Li et al (2008) showed that the summertime nocturnal precipitation in the Sichuan Basin is contributed mainly by long-duration precipitating systems. In addition, the diurnal cycle of precipitation presents an eastward delayed diurnal phase from the east of the Tibetan Plateau (TP) down to the Yangtze River valley in central China Huang et al 2010;Bao et al 2011;Yuan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional and/or seasonal differences of diurnal rainfall patterns not only occur in China [8,[18][19][20], but also exist in other regions of the world, like in Japan [21], island regions in Asia [22,23], the Asian monsoon region [10][11][12], marine continental islands [24,25], northwest South America [26], the United States Great Plains [27], the Andes in South America [28,29], Africa [30] and even the global tropics [31,32]. The convective rainfall maximum late at night or in the early-morning hours over oceans can be explained by radiation-convection interaction theory [33,34].…”
mentioning
confidence: 99%